2013
DOI: 10.22226/2410-3535-2013-4-268-271
|View full text |Cite
|
Sign up to set email alerts
|

Modified aluminosilicate wastes for ceramic building materials

Abstract: Установлено, что одним из методов модифицирования алюмосиликатных отходов является помол. Определены оптимальные режимы помола в условиях лаборатории. Проведены физико-химические исследования модифи-цированной золы методами РФА, ДТА и микроскопии. Показано, что модифицированные золы ТЭС при ис-пользовании их в производстве керамического кирпича, положительно влияют на технологические характери-стики сырца, а также готовых изделий.Ключевые слова: керамический кирпич, зола ТЭС, моди-фицирование.It is known that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…According to the planning matrix, an experiment was conducted, the adequacy of the obtained regression equations was checked, and nomograms were constructed Analysis of nomograms to determine the optimal pressing pressure (Fig. 1) after separate grinding showed that it was possible to obtain the ceramic brick brands from M120 to M225 with satisfying physical and mechanical properties, where the average density is in the range from 1,6 to 1,98 g / cm 3 and with water absorption 12-14 %. The selected areas determine the optimal pressure in the range from 19,5 to 20,5 MPa, which is confirmed by the previous studies [6].…”
Section: Materials and Technologies In Construction And Architecture IImentioning
confidence: 99%
See 2 more Smart Citations
“…According to the planning matrix, an experiment was conducted, the adequacy of the obtained regression equations was checked, and nomograms were constructed Analysis of nomograms to determine the optimal pressing pressure (Fig. 1) after separate grinding showed that it was possible to obtain the ceramic brick brands from M120 to M225 with satisfying physical and mechanical properties, where the average density is in the range from 1,6 to 1,98 g / cm 3 and with water absorption 12-14 %. The selected areas determine the optimal pressure in the range from 19,5 to 20,5 MPa, which is confirmed by the previous studies [6].…”
Section: Materials and Technologies In Construction And Architecture IImentioning
confidence: 99%
“…By changing the amount of molding moisture in the press powder of the recommended composition from 8 to 12 % and the spent pressing pressure of 20 MPa (Fig. 2), the area for obtaining the highquality ceramic bricks from M120 to M250 increases, the growing strength of the ceramic samples is characterized by a high average density of more 1,9 g/cm 3 , but the amount of the silicate-clump injected also increases from 10 to 12,5 % by mass, which leads to the ceramic mass supersaturation with the eutectic melt.…”
Section: Materials and Technologies In Construction And Architecture IImentioning
confidence: 99%
See 1 more Smart Citation